L'application des règles d'interprétation constitutionnelle - Langlois, Raynold (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
With the advent of the Charter of Rights, the field of Constitutional Law is no longer reserved to a few scholars. The fundamentals at least of the art of constitutional interpretation must be part of the daily arsenal of every lawyer. Constitutional interpretation is by no means mechanical. Constitutional enactments must develop and grow like a living tree. They must be read and applied with a degree of political sensitivity, historical perspective and a good deal of common sense. We must draw on the wealth of constitutional precedents and authorities gathered since 1867 especially for the first stage of Charter interpretations where the content of the rights intended for protection is analysed. New rules are being developed for the second stage where an attempt is made to save conflicting laws on the basis of a section 1 "reasonable limit (...) demonstrably justified in a free and democratic society."